Gambaran Spiritualitas Mahasiswa Ners Tingkat 2 di Rumah pada Masa Pandemi Covid-19 di STIKes Santa Elisabeth Medan Tahun 2020 - Lindawati Simorangkir (STIKes Santa Elisabeth Medan, 2021)
Background: The Covid-19 epidemic hit the world and claimed many victims so that the government is trying to break the chain of spreading the Covid-19 Virus, but for all spiritual services to the people it must continue, therefore the church cannot stop, nor in any situation because it is a shepherding duty for the sake of fulfillment of spirituality needs because spirituality is one's awareness in appreciating the meaning of life towards God, and noble values, thus inspiring hope, humility, compassion, sincerity, and harmony in everyday life both towards God, oneself, others and the environment. This study aims to identify the Spirituality Picture of Level 2 Nurse Students at Home during the Covid-19 Pandemic at STIKes Santa Elisabeth Medan in 2020.Methods: This type of quantitative research with a descriptive design. The population of all students Ners level 2 was 88 people, the sampling technique was: total sampling.Results: The results of this study showed: 82 people in high category (93,2%) and 6 people in medium category (6,8%), it can be concluded that most of the spirituality of Nurse students level 2 was in the high category.Conclusion: Therefore, it is hoped that students will maintain their spirituality and improve their spirituality by collaborating with others, protecting the environment, helping or sharing with people around us because God and others (Vertical & Horizontal) cannot be separated because of a connection.